The relationship between role conflict, work overload, interpersonal communication and job stress among Royal Malaysia Police Officer - Ng, Hooi Yee (2018)
The purpose of this study is to examine the relationship between role conflict, work overload, interpersonal communication and job stress among Royal Malaysia Police Officers. This study was conduct in Royal Police Headquarters Contingent Kedah. A total of 234 questionnaires were distributed among police officers that become the respondents for this research. In this entire study, the data were gathered through questionnaires and was analyzed through statistical model such as descriptive, reliability and multiple regression analysis. All these analysis are used to answer research question, objective and hypothesis in this research study. As a conclusion, the results showed that there had not significant relationship between role conflict, work overload, interpersonal communication and job stress among Royal Malaysia Police Officers.